The antibacterial effect of photodynamic therapy in dental plaque-derived biofilms - Fontana, C. R. [UNESP]; Abernethy, A. D.; Som, S.; Ruggiero, K.; Doucette, S.; Marcantonio, Rosemary Adriana Chierici [UNESP]; Boussios, C. I.; Kent, R.; Goodson, J. M.; Tanner, A. C. R.; Soukos, N. S. (Wiley-Blackwell Publishing, Inc, 2009)
Background and Objective: Photodynamic therapy has been advocated as an alternative to antimicrobial agents to suppress subgingival species and to treat periodontitis. Bacteria located within dense biofilms, such as those encountered in dental plaque, have been found to be relatively resistant to antimicrobial therapy. In the present study, we investigated the ability of photodynamic therapy to reduce the number of bacteria in biofilms by comparing the photodynamic effects of methylene blue on human dental plaque microorganisms in the planktonic phase and in biofilms.Material and Methods: Dental plaque samples were obtained from 10 subjects with chronic periodontitis. Suspensions of plaque microorganisms from five subjects were sensitized with methylene blue (25 mu g/mL) for 5 min then exposed to red light. Multispecies microbial biofilms developed from the same plaque samples were also exposed to methylene blue (25 mu g/mL) and the same light conditions as their planktonic counterparts. In a second set of experiments, biofilms were developed with plaque bacteria from five subjects, sensitized with 25 or 50 mu g/mL of methylene blue and then exposed to red light. After photodynamic therapy, survival fractions were calculated by counting the number of colony-forming units.Results: Photodynamic therapy killed approximately 63% of bacteria present in suspension. By contrast, in biofilms, photodynamic therapy had much less of an effect on the viability of bacteria (32% maximal killing).Conclusion: Oral bacteria in biofilms are affected less by photodynamic therapy than bacteria in the planktonic phase. The antibacterial effect of photodynamic therapy is reduced in biofilm bacteria but not to the same degree as has been reported for treatment with antibiotics under similar conditions.
Keywords: dental plaque bacteria; planktonic phase; biofilms; photodynamic therapy